Answer:
Step-by-step explanation:
Given that:
As we know that the Parabola is of type :
[tex](x - x_{0}) ^{2}[/tex] = -4a(y -[tex]y_{0}[/tex] ) where: [tex]x_{0} y_{0}[/tex] is the origin of the line so we have:
[tex]x_{0} = 0[/tex] and [tex]y_{0} = 20[/tex]
<=> [tex]x^{2}[/tex] = -4a(y-20)
at y = 0, we have:
[tex]x^{2}[/tex] = -4a(0-20)
<=> [tex]x^{2} = 80a[/tex]
<=> x = ±[tex]\sqrt{80a}[/tex]
But we know that 2x= 80 <=> x= 40, so:
40 = [tex]\sqrt{80a}[/tex]
<=> 1600 = 80a
<=> a = 20
The equation for the parabola is: [tex]x^{2} = 80(y-20)[/tex]
It's height from the center at x= 0 => y= 20